Effects of intrarenal afferent stimulation by bradykinin on renal sympathetic nerve activity: tonic inhibition contributing to renal function - Eva Hutter; Tilmann Ditting; Martin Hindermann; Karl F. Hilgers; Roland E. Schmieder; Christian Morath; Mario Schiffer; Kerstin Amann; Roland Veelken; Kristina Rodionova (Pflügers Archiv - European Journal of Physiology, 2025)
Bradykinin (BK) may increase renal sodium excretion by decreasing tubular ENaC activity. Afferent renal nerve activity (ARNA) putatively controls renal sympathetic nerve activity (RSNA) involved in renal sodium handling. We recently found tonic sympatho-inhibition due to intrarenal ARNA stimulation by the TRPV1 agonist capsaicin (CAP). Since BK is known to augment TRPV1 effects, we hypothesized that intrarenally applied BK also tonically inhibits RSNA. Four groups of rats (n = 8; BK, CAP, HOE + BK, NaCl-control) were equipped with arterial and venous catheters for blood pressure (BP) and heart rate (HR) recordings and drug application; bipolar electrodes for RSNA and ARNA recordings, renal arterial catheter for intrarenal administration (IRA) of bradykinin (BK: 10 −5 M, 20 µl and 10 –4 M; 2.5, 5, 10 µl), capsaicin (CAP 3.3, 6.6, 10 and 33*10 −7 M, 10 µl). The B2-receptor antagonist HOE-140 (10 –4 M, 40 µl) was administered intravenously (IV) just before IRA BK (HOE + BK), finally the NK 1 -receptor blocker RP67580 (10 −2 M, 15 µl; IV) was applied in all groups at the end of the experiment. IRA BK and CAP momentarily increased ARNA. IRA CAP, IRA BK, and IRA HOE + BK, decreased RSNA from 4.2 ± 0.8 to 1.3 ± 0.2 µV*sec (BK, P < 0.01), 3.6 ± 0.5 to 0.9 ± 0.2 µV*sec (CAP, P < 0.01) and 3.2 ± 0.3 to 0.8 ± 0.1 µV*sec (HOE-BK, P < 0.01). Suppressed RSNA (BK, CAP, HOE + BK) was unmasked by IV RP67580: 1.6 ± 0.5 to 8.6 ± 2.9 µV*sec (BK, P < 0.01); 1.0 ± 0.2 to 6.1 ± 1.5 µV*sec (CAP, P < 0.01); 0.8 ± 0.2 to 4.5 ± 0.8 µV*sec (HOE-BK, P < 0.05). IRA BK was associated with momentary increases of RSNA, abolished by HOE-140. Intrarenal stimulation of renal afferent nerves by BK induced tonic renal sympathodepression likely augmenting sodium and water excretion.

P17-08 Integrating motility tracking and high-content morphological image analysis for predictive immunotoxicology - A. Martin; R. Mahendran; E. Hoffman; M. Silva; K. Schaffer; A. Jötten; P. Paulitschke; V. Hutter (Toxicology Letters, 2025)

Increasing microplastic concentrations have nonlinear impacts on the physiology of reef-building corals - Vanessa Tirpitz; Mona Hutter; Hanna Hutter; Julia Prume; Martin Koch; Thomas Wilke; Jessica Reichert (Science of The Total Environment, 2025)

Can TK-TD modelling bridge the gap between in vitro and in vivo mammalian toxicity data? - Thomas Martin; Mark E. Hodson; Helen Thompson; Victoria Hutter; Roman Ashauer (Toxicology in Vitro, 2024)

Profiling alveolar macrophage responses to inhaled compounds using in vitro high content image analysis - Ewelina Hoffman; Laura Urbano; Abigail Martin; Rhamiya Mahendran; Aateka Patel; Darragh Murnane; Clive Page; Lea Ann Dailey; Ben Forbes; Victoria Hutter (Toxicology and Applied Pharmacology, 2023)

Aerosol measurement identifies SARS-CoV 2 PCR positive adults compared with healthy controls - Desireé Gutmann; Gerhard Scheuch; Timon Lehmkühler; Laura-Sabine Herrlich; Anton Landeis; Martin Hutter; Christoph Stephan; Maria Vehreschild; Yascha Khodamoradi; Ann-Kathrin Gossmann; Florian King; Frederik Weis; et al. (Environmental Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Morphometric Characterization of Rat and Human Alveolar Macrophage Cell Models and their Response to Amiodarone using High Content Image Analysis - Ewelina Hoffman; Aateka Patel; Doug Ball; Jan Klapwijk; Val Millar; Abhinav Kumar; Abigail Martin; Rhamiya Mahendran; Lea Ann Dailey; Ben Forbes; Victoria Hutter (Pharmaceutical Research, 2017)

No correlation between NF1 mutation position and risk of optic pathway glioma in 77 unrelated NF1 patients - Sonja Hutter; Rosario M. Piro; Sebastian M. Waszak; Hildegard Kehrer-Sawatzki; Reinhard E. Friedrich; Alvaro Lassaletta; Olaf Witt; Jan O. Korbel; Peter Lichter; Martin U. Schuhmann; Stefan M. Pfister; Uri Tabori; et al. (Human Genetics, 2016)

Expression of multiple membrane-associated phospholipase A1 beta transcript variants and lysophosphatidic acid receptors in Ewing tumor cells - Benjamin Joachim Schmiedel; Christoph Hutter; Manuela Hesse; Martin Sebastian Staege (Molecular Biology Reports, 2011)

Selection of patients with germline MLH1 mutated Lynch syndrome by determination of MLH1 methylation and BRAF mutation - Hanifa Bouzourene; Pierre Hutter; Lorena Losi; Patricia Martin; Jean Benhattar (Familial Cancer, 2010)

CENTROPE - Martin Hutter (Standort, 2009)